LITERASI INFORMASI: KEMAMPUAN PENTING ABAD 21 DAN PEMETAANNYA DI SEKOLAH DALAM MENGHADAPI ASESMEN NASIONAL - Zainul Mustofa (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2022)
Students as the nation’s next generation are expected to master information literacy, but unfortunately, false information is still circulating even though there is a preventive program such as “Gerakan Literasi Sekolah” (or School Literacy Movement). This study aims to describe the initial profile of students’ information literacy in the global era to prepare for the implementation of the national assessment. The subjects of the study were 105 Vocational High School (SMK) students in the Bululawang District. Quantitative descriptive research was conducted to map students’ information literacy skills. The study found that the average result for students’ information literacy skill was in the category of needing special intervention with a score of 34.4. Furthermore, there was no significant difference between the information literacy skill of male and female students. Moreover, the students’ information literacy skill was divided into three categories, i.e.: 1) need special intervention (62.9%), 2) basic (30.5%), and 3) proficient (6.7%). The lack of information literacy skill was resulted from their tendency to use assumptions or intuition rather than absorbing and managing the information. Based on these data, it is essential to improve the quality of students’ literacy skills by improving the facilities, programs, and evaluation of the School Literacy Movement.